Modification of structural and functional characteristics of brewer's spent grain protein by ultrasound assisted extraction. (March 2021) - Li, Wanying; Yang, Huirong; Coldea, Teodora Emilia; Zhao, Haifeng
Abstract: Ultrasound assisted extraction (UAE) was applied to enhance the extraction efficacy of protein from brewer's spent grain (BSG). The effects of ultrasonic extraction conditions including power, time and duty cycle on the techno-functional properties of protein were also evaluated. The results demonstrated that in 110 mM sodium hydroxide solution, UAE working at 250 W for 20 min under duty cycle of 60% could significantly improve the protein yield to 86.16% compared with traditional extraction without ultrasound (45.71%). The structural analysis including CD, UV–Vis, SH content results and SDS-PAGE patterns clearly showed that BSG protein was modified under ultrasonication. The extracted BSG protein increased 5.83% of β-sheet content while decreased α-helix, β-turn and random coil contents by 4.76%, 0.33% and 0.74%, respectively. Besides, SDS-PAGE pattern of protein was slightly strengthened. The enhancement in SH content and UV–Vis spectra further indicated that exposure and unfolding of protein structure occurred and thus the functional properties of BSG protein were enhanced. Indeed, fat absorption capacity, emulsifying and foaming properties of BSG protein treated by UAE were all improved except for the water absorption capacity. Thus, UAE could be a promising method to separate protein from this valuable feedstock for further utilization in the food industry. Highlights: Ultrasound assisted extraction improved the extraction efficiency of BSG protein. The structural characteristics of BSG protein were modified after UAE. The functional properties of BSG protein were enhanced after UAE. UAE under continuous mode was proven to be unsuitable in BSG protein recovery.